Time-resolved fluorescence based direct two-site apoA-I immunoassays and their clinical application in patients with suspected obstructive coronary artery disease - Negi, Priyanka; Heikkilä, Taina; Vuorenpää, Karoliina; Tuunainen, Emilia; Nammas, Wail; Maaniitty, Teemu; Knuuti, Juhani; Metso, Jari; Lövgren, Janita; Jauhiainen, Matti; Lamminmäki, Urpo; Pettersson, Kim; et al. (Frontiers in Cardiovascular Medicine, 2022)
Objective: High density lipoprotein (HDL) is a heterogenous group of subpopulations differing in protein/lipid composition and in their anti-atherogenic function. There is lack of assays which can target the functionality of HDL particles related to atherosclerosis. The objective of this study was to construct two-site apolipoprotein A-I (apoA-I) assays and to evaluate their clinical performance in patients with suspected obstructive coronary artery disease (CAD). Approach and Results: Direct two-site apoA-I assays (named 109-121 and 110-525) were developed to identify apoA-I present in the HDL of patients with CAD using apoA-I antibodies as a single chain variable fragment fused with alkaline phosphatase. ApoA-I109-121 and apoA-I110-525 were measured in 197 patients undergoing coronary computed tomography angiography and myocardial positron emission tomography perfusion imaging due to suspected obstructive CAD. Among patients not using lipid lowering medication (no-LLM, n=125), the level of apoA-I110-525 was higher in the presence than in the absence of coronary atherosclerosis [21.88 (15.89-27.44) mg/dL vs 17.66 (13.38-24.48) mg/dL, P = 0.01)], whereas there was no difference in apoA-I109-121, HDL cholesterol and apoA-I determined using polyclonal apoA-I antibody. Levels of apoA-I109-121 and apoA-I110-525 were similar in the presence or absence of obstructive CAD. Among patients not using LLM, apoA-I110-525 adjusted for age and sex identified individuals with coronary atherosclerosis with a similar accuracy to traditional risk factors [AUC (95% CI): 0.75(0.66-0.84) vs Framingham risk score 0.71 (0.62-0.81)]. However, a combination of apoA-I110-525 with risk factors did not improve accuracy [AUC (95% CI): 0.73 (0.64-0.82)]. Conclusion: Direct two-site apoA-I assays recognizing heterogeneity in reactivity with apoA-I could provide a potential approach to identifying individuals at risk of coronary atherosclerosis. However, their clinical value remains to be studied in larger cohorts.